Harmonization of the Mudharabah Concept in Fiqh Muamalah with the Establishment Mechanism of Sharia Limited Liability Companies in Indonesia - Syahrida Syahrida; Zulfikri Zulfikri; Putri Ramadhaniah; Arifin Arifin; Geofanny Guruh Hasintongan Sianipar (Faculty of Law, Universitas Pekalongan, 2025)
This article examines the harmonization between the mudharabah contract concept in fiqh muamalah and the mechanism for establishing Sharia Limited Liability Companies (LLCs) in Indonesia. The mudharabah contract, which bases business partnerships on a profit-sharing principle between the capital owner (shahibul maal) and the business manager (mudharib), is characterized by trust, fairness, and transparency. Meanwhile, a Sharia LLC is a modern legal entity governed by national statutory regulations, with a formal and structured legal framework. Using a normative-juridical approach and comparative analysis, this article explores the intersections and potential conflicts between these two systems and formulates an integrative model that allows for the substantive application of Sharia values embedded in mudharabah within the legal framework of an LLC. The findings reveal that the fundamental principles of mudharabah can be adopted in the design of institutional structures, governance, and decision-making mechanisms within a Sharia LLC, without violating positive law. These findings underscore the importance of reconstructing Islamic legal thought to be responsive to the dynamics of modern law and promote the development of Sharia business models that are legally recognized and aligned with the maqashid shariah.